State Graduation Requirements for Students with and without Disabilities. Executive Summary - Thurlow, Martha; Shin, Hyeonsook; Guy, Barbara; Lee, Sun-Young; National Transition Network, Minneapolis, MN. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1999)
This report discusses outcomes of a study of assessment directors and transition specialists from each of the 50 states and the District of Columbia on exit documents available to and graduation requirements for students with and without disabilities. Results indicate: (1) approximately 80 percent of the states have alternative exit documents for students; (2) states have raised and are continuing to raise their high school graduation requirements; (3) some states allow flexibility for students with disabilities in meeting graduation requirements in multiple ways, including Individualized Education Program (IEP) completion, modified coursework, and exemption from an exit exam; (4) modified coursework to meet course credit requirements is the most common type of change provided to students with disabilities; (5) IEP completion is not a universally accepted way for students with disabilities to earn a standard diploma; (6) states with graduation exams generally had more exit documents available to students but less flexibility in how students with disabilities could meet standard diploma requirements; (7) almost all states that did not allow changes in standard diploma requirements for students with disabilities had at least two exit documents available to these students; and (8) most states with graduation exams had records of the participation and performance of their students with disabilities in those exams. (CR)
Availability: National Transition Network, Institute on Community Integration (UAP), University of Minnesota, 103 U-Tech Center, 1323 SE 5th St., Minneapolis, MN 55414; Tel: 612-627-4008; Fax: 612-624-1998.
Sponsoring Agency: Office of Special Education and Rehabilitative Services (ED), Washington, DC.
Contract Number: H158M50001.
Contract Number: H159C50001.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Accommodations (Disabilities); Academic Standards; Access to Education; Degree Requirements; Disabilities; Educational Testing; Graduation Requirements; High Schools; State Regulation; State Standards; Reports, Research